The answer is <span>x - 1 = 3x + 9

All steps are:

</span>Step 1: 4ˣ⁻¹ = 64ˣ⁺³<span>

Step 2: 4</span>ˣ⁻¹ = (4³)ˣ⁺³ <span>

Step 3: 4</span>ˣ⁻¹ = 4³ˣ⁺⁹

Step 4: x - 1 = 3x + 9

Step 5: x - 3x = 1 + 9

Step 6: -2x = 10

Step 7: x = 10/-2

Step 8: x = -5

**Answer:**

inequality

**Step-by-step explanation:**

Inequality are two or more expressions joined by an inequality sign is called

**Answer:**

propotianal

**Step-by-step explanation:**

Rise is how many you go up on the y axis x axis is how many you go to the left or right on the x axis if the number is negative you go the the right. the points match up with -4/1 - 1 so it's is proportional please give me brainliest

The area of the parallelogram is...

**Answer:**

**Step-by-step explanation:**

6x-3y+10=0 ⇒-3y=-6y-10 ⇒ y=-6x/-3 -10/-3⇒ y=2x+10/3

2x -y +9 =0 ⇒ -y=-2x-9 ⇒y=2x+9

<h2>y=2x+10/3</h2><h2>y=2x+9</h2><h2 /><h2 />